Assessment of the educational needs of patients with chronic renal Insufficiency (Journal of Hama University, 2022)
Chronic renal insufficiency affects the patient's life significantly and is considered one of the most common diseases with severe consequences, severe disability and high treatment costs. Therefore, the current descriptive study aimed to determine the level of educational needs of patients with chronic renal failure. And that is when a convienent sample consists of 50 dialysis patients in the industrial hemodialysis department at the National Hospital in Lattakia. The data were collected using a questionnaire developed by the researcher, where the study showed that 92% of patients had a high level of educational needs related to treatment and disease progression. And that 88% have a high level of educational needs related to the physical axis. And 72% have a high level of educational needs related to the diet axis. The study recommended the development of educational programs for patients with chronic renal failure and the development and design of educational leaflets and brochures to spread awareness and knowledge about the disease.